Significant Atmospheric Boundary Layer Change Observed above an Agulhas Current Warm Cored Eddy - C. Messager; S. Swart (Advances in Meteorology)
The air-sea impact of a warm cored eddy ejected from the Agulhas Retroflection region south of Africa was assessed through both ocean and atmospheric profiling measurements during the austral summer. The presence of the eddy causes dramatic atmospheric boundary layer deepening, exceeding what was measured previously over such a feature in the region. This deepening seems mainly due to the turbulent heat flux anomaly above the warm eddy inducing extensive deep and persistent changes in the atmospheric boundary layer thermodynamics. The loss of heat by turbulent processes suggests that this kind of oceanic feature is an important and persistent source of heat for the atmosphere.